AN INTRODUCTION TO THE DISTRIBUTION OF FICUS - E. J. H. CORNER (REINWARDTIA, 1958)
Ficus displays many problems fundamental to the distribution of tropical plants. As a natural g-enus, one of the most derived of its family, it shows that these problems refer not to the origin of the genus or of its major groups, but to the subsequent course of sectional evolution. Detailed morphological revision must, therefore, precede phytogeography. The facts, here epitomised, are based on monographic revision of the species of Asia and Australasia, and have not been called from other writings. Seed-dispersal in Ficus must be accompanied by dispersal of the pollinating wasp. It seems true, as Beccari pointed out, that the large banyans have an advantage in this respect over small trees impeded by the dense forest.Two subgenera, Pharmaeosycea and Urostigma, suggest a southern migration, but the third subgenus Ficus suggests a northern origin and dispersal. Pharmaeosycea, hitherto regarded as American, has 46 species in Asia and Australasia, and it comprises most of the fig-flora of New Caledonia (26 species in all, 20 endemic species of Pharmaeosycea). Ficus prolixa (Polynesia) seems related to sect. Americana of Urostigma. The F. elastica group (Queensland, Papua, Solomon Islands) seems related to the African sect. Bibracteata of Urostigma. The F, benghalensis group parallels the distribution of the Dipterocarpaceae, but does not occur in Africa.